Fertility preservation: a challenge for IVF-clinics. (November 2015) - Dahhan, Taghride; Mol, Femke; Kenter, Gemma G.; Balkenende, Eva M.E.; de Melker, Annemieke A.; van der Veen, Fulco; Dancet, Eline A.F.; Goddijn, Mariëtte
Abstract: Objective: Acute fertility preservation for women is an interdisciplinary treatment that requires adequate information provision and early referral. This quality management project aimed to improve fertility preservation care by using a practical tool: Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis. Study design: Quality management project was executed between May 2011 and July 2013. This project has been executed in a university affiliated IVF-clinic in cooperation with two oncological sites and used a four-step strategy: (1) monitoring baseline referral process, (2) exploring baseline fertility preservation program by Strengths, Weaknesses, Opportunities and Threats' (SWOT)-analysis, (3) setting up a new fertility preservation program and (4) evaluating the new fertility preservation program by means of SWOT-analysis. Results: During the three-months monitoring period, fertility preservation was requested for a total of 126 women. The mean age of the women was 33.8 years old (range 1–42 years old). Most requests came from women who wanted to cryopreserve oocytes because of age-related decline of fertility ( n  = 90; 71%). Most requests for acute fertility preservation concerned women with breast cancer ( n  = 16; 57%). Information leaflets and pre-consultation questionnaires for women improved the quality of first fertility preservation consultation as evaluated by final SWOT-analysis. Collaboration with oncological centres and information about fertility preservation improved the referral process. Conclusions: SWOT-analysis proved useful for setting up a new fertility preservation-program and can be recommended as a tool to improve the management and organisation of new types of reproductive care.